Viable System Model as A Framework for Value Co-Creation Service System Analysis of Technology-based Business Incubator - Eka Yuliana; Utomo Sarjono Putro; Pri Hermawan; Astri Ghina (Jurnal Manajemen Indonesia, 2023)
Bandung Techno Park (BTP) at Telkom University has a crucial role in the technology-based business incubation scheme. From the recruitment process, learning goals, venture capital, commercialization with all impacted to start-ups accomplishment. These observations resulted by using qualitative research methods for one year. Referring to the concept of service systems, it was founded that business incubators in higher education can produce the holistic service system diagnostics to develop the external collaboration between university and industry. These findings are successfully set out by used the Viable System Model (VSM) from service system science approach which is divided into five main functions: (1) Operationalization, (2) Coordination, (3) Monitoring and Control, (4) Intelligence, (5) Policy. The important collaboration of the integrated service system at BTP is framed in a structured concept. Incubator operation supervision focuses on service systems that play a role in four types of management, namely: business innovation and incubation, tenant service and support, marketing, and technology solutions. The findings of the analysis with VSM relate to the role of technology-based business incubators in creating value co-creation from a service science point of view. Keywords— Value Co-creation; New Technology-based Firms; Business Incubators; University-industry Collaboration